2021
DOI: 10.1002/prp2.892
|View full text |Cite
|
Sign up to set email alerts
|

Real clinical impact of drug–drug interactions of immunosuppressants in transplant patients

Abstract: The main objective was to determine the prevalence of real drug–drug interactions (DDIs) of immunosuppressants in transplant patients. We conducted a prospective, observational 1‐year study at a tertiary hospital, including all transplanted patients. We evaluated data from monitoring blood concentrations of immunosuppressive drugs and adverse drug events (ADEs) caused by DDIs. The DDIs were classified as C, D, or X according to their Lexi‐Interact rating (C = monitor therapy, D = consider therapy modification,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
1
12
1
Order By: Relevance
“…6 The use of many drugs increases the risk of adverse reactions and drug interactions, which can lead to treatment withdrawal, further contributing to the non-compliance of the transplant recipient with drug therapy. 38,39 Adherence to treatment is an important factor for successful transplantation to avoid acute rejection and graft loss, so transplant patients need specific care with adequate instructions. 40 When comparing our results with those of Melchiors, Correr and Fernandez-Llimos, who employed MRCI in diabetic patients, we found that the relation between score and number of medications was divergent.…”
Section: Discussionmentioning
confidence: 99%
“…6 The use of many drugs increases the risk of adverse reactions and drug interactions, which can lead to treatment withdrawal, further contributing to the non-compliance of the transplant recipient with drug therapy. 38,39 Adherence to treatment is an important factor for successful transplantation to avoid acute rejection and graft loss, so transplant patients need specific care with adequate instructions. 40 When comparing our results with those of Melchiors, Correr and Fernandez-Llimos, who employed MRCI in diabetic patients, we found that the relation between score and number of medications was divergent.…”
Section: Discussionmentioning
confidence: 99%
“…Transplant recipients are at considerable risk of adverse effects from drug interactions due to polypharmacy, the narrow therapeutic index of immunosuppressants, and the vulnerability of CNI to CYP3A4‐ and p‐glycoprotein‐mediated drug interactions. Up to 1 in 5 transplant recipients have a clinically significant drug interaction, which can contribute to adverse drug effects 58 . Transplant recipients starting azole antifungal agents should be evaluated for the need to adjust immunosuppression (e.g., CNI and mTORi) and non‐immunosuppressant therapies (e.g., statins, proton pump inhibitors, calcium channel blockers) as the result of drug interactions 26,59,60 .…”
Section: Navigating Drug Interactionsmentioning
confidence: 99%
“…Up to 1 in 5 transplant recipients have a clinically significant drug interaction, which can contribute to adverse drug effects. 58 Transplant recipients starting azole antifungal agents should be evaluated for the need to adjust immunosuppression (e.g., CNI and mTORi) and nonimmunosuppressant therapies (e.g., statins, proton pump inhibitors, calcium channel blockers) as the result of drug interactions. 26,59,60 Importantly, the extent of a drug interaction and its clinical significance differs between agents within this medication class.…”
Section: Navig Ating Drug Inter Ac Tionsmentioning
confidence: 99%
“…Due to polypharmacotherapy, ICU lung transplant recipients are at a greater risk for pDDIs. Especially pDDIs involving immunosuppressive drugs with a limited therapeutic index are particularly susceptible to adverse drug events (ADEs) ( Gago-Sánchez et al, 2021 ; Dewey et al, 2023 ). The tendency is complicated by illness severity and organ failure, which can alter medication pharmacologic response.…”
Section: Introductionmentioning
confidence: 99%